Coamplification of Leucocytozoon by PCR diagnostic tests for avian malaria: a cautionary note. - Cosgrove, C; Day, K; Sheldon, B (2006)
A number of PCR assays have now been described for detecting species of the avian malaria parasites Plasmodium and Haemoproteus from blood samples. The published protocols amplify both genera simultaneously, owing to the high degree of sequence similarity between them in target genes. However, the potential for coamplification in these assays of a third, closely related hematozoan parasite, Leucocytozoon spp. has been largely overlooked. In this paper, we highlight the importance of this issue, showing that coamplification of Leucocytozoon spp. occurs in several of the protocols designed to amplify avian malaria parasites. This leads not only to scoring of false positives but, in cases of mixed Leucocytozoon/malaria infections, may also lead to scoring of false negatives. We, therefore, advocate the use of a post-PCR diagnostic step, such as RFLP analysis or sequencing, to assess the contribution of Leucocytozoon spp. to overall prevalence.